Meningkatkan Motorik Halus Anak Melalui Kegiatan Menjiplak Dengan Media Alam Di Paud Bintang Cemerlang - Nelis Hayati; Asnawati Asnawati; Ranny Fitria Imran (Early Childhood Research and Practice, 2026)
This study aims to enhance the fine motor skills of children at PAUD Bintang Cemerlang through tracing activities using natural materials. The study employed the Classroom Action Research (CAR) method, conducted over two cycles; each cycle consisted of planning, action implementation, observation, and reflection stages. The research subjects comprised 12 children. Data collection was carried out through observation and documentation. Data analysis was performed using descriptive quantitative methods, utilizing percentages to track the development of the children's fine motor skills. The results indicate that tracing activities using natural materials can improve the fine motor skills of early childhood learners. This improvement was evident across each learning cycle. In Cycle I, Meeting 1, the children's fine motor skills achieved a score of 40.41% (categorized as "Beginning to Develop" or MB), rising to 50% in Cycle I, Meeting 2. Subsequently, in Cycle II, Meeting 1, the score increased to 62.5% (categorized as "Developing as Expected" or BSH), and in Cycle II, Meeting 2, it reached 81.25% (categorized as "Developing Very Well" or BSB). Improvements in fine motor skills were observed in the children's ability to hold writing instruments, follow tracing patterns, control hand movements, and produce work that was neater and more controlled. The use of natural materials—such as leaves, flowers, and twigs—fostered greater interest and enthusiasm among the children during learning activities. Thus, tracing activities using natural materials proved effective in enhancing the fine motor skills of early childhood learners at PAUD Bintang Cemerlang.